DoRiNA 2.0—upgrading the doRiNA database of RNA interactions in post-transcriptional regulation - Blin, Kai; Dieterich, Christoph; Wurmus, Ricardo; Rajewsky, Nikolaus; Landthaler, Markus; Akalin, Altuna (Nucleic acids research, 2015)
The expression of almost all genes in animals is subject to post-transcriptional regulation by RNA binding proteins (RBPs) and microRNAs (miRNAs). The interactions between both RBPs and miRNAs with mRNA can be mapped on a whole-transcriptome level using experimental and computational techniques established in the past years. The combined action of RBPs and miRNAs is thought to form a post-transcriptional regulatory code. Here we present doRiNA 2.0, available at http://dorina.mdc-berlin.de. In this highly improved new version, we have completely reworked the user interface and expanded the database to improve the usability of the website. Taking into account user feedback over the past years, the input forms for both the simple and the combinatorial search function have been streamlined and combined into a single web page that will also display the search results. Especially, custom uploads is one of the key new features in doRiNA 2.0. To enable the inclusion of doRiNA into third-party analysis pipelines, all operations are accessible via a REST API. Alternatively, local installations can be queried using a Python API. Both the web application and the APIs are available under an OSI-approved Open Source license that allows research and commercial access and re-use.